Pirate hunters : treasure, obsession, and the search for a legendary pirate ship - Kurson, Robert (Random House, 2015)
Traces the high-stakes quest of John Mattera and Shadow Divers' Chatterton to find the lost pirate ship of Joseph Bannister, discussing their teamwork with technology-eschewing Tracy Bowden and the story behind Bannister's elusive treasure.